Factors influencing accidents and injuries in the artisanal and small-scale gold mining industry in Ghana: A case of Adadiem in the Jaman North district of Ghana - Ebenezer Kwadwo Siabi; Peter Donkor; Michael Kwasi Sieh; Kwasi Frimpong; Samuel Kofi Mensah; Sarah Elikplim Siabi; Christopher Vuu (Heliyon, 2025)
Globally, prioritizing the safety of workers and their immediate evironment remain an important agenda in contemporary societies. Regardless, the artisanal and small-scale gold mining (ASGM) industry in Ghana is fraught with accidents and injuries making it one of the most hazardous undertakings in the country. This study was undertaken to determine the prevalent occupational accidents/injuries characterizing Ghana's ASGM industry and to establish the specific types and underlying causes of injuries that occur during ASGM activities as the intricate factors which wield influence over the ASGM's compliance with safety regulations in Ghana. A structured questionnaires and interview guide were used to collect data from 248 survey respondents. Likelihood ratio test regression, Chi-square test and descriptive statistics were performed to test the relationship among study factors. The results of the study reveal struck-by and slipping/falling as the most prevalent safety hazards, resulting in minor injuries. Working tools and machinery were revealed as the primary sources of injuries, with the legs, knees, and feet being the most frequently affected areas. The findings unequivocally point to multiple OSH violations within the ASGM industry in the Adadiem region. In light of these findings, we propose that the Government of Ghana (GoG) takes action by implementing and rigorously enforcing legislation that imposes stringent requirements on ASGM operators, compelling them to uphold OSH standards and safeguard the well-being of their workforce. Furthermore, we suggest policy instruments, such as fines, taxes, restrictions and subsidies, may be strategically employed to incentivize and ensure compliance with safety regulations.